2001
DOI: 10.1123/jsm.15.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Do Differences Make a Difference? Managing Diversity in Division IA Intercollegiate Athletics

Abstract: This study applies a framework of diversity initiatives as a basis of exploration into top management beliefs and diversity management strategies of Division IA intercollegiate athletic organizations. This framework utilizes issues of power, demographic and relational differences, and past literature regarding specific diversity strategies to empirically assess these organizations' outlooks regarding employee diversity. Results of the study suggest that Division IA intercollegiate athletic organizations operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 17 publications
6
98
0
1
Order By: Relevance
“…Specifically, the responses to quid pro quo harassment were stronger in proactive athletic departments (M=4.32, SD=.85) than they were in compliant departments (M=4.00, SD=1.00), d=.35. Thus, while organizational culture did not have direct effects, these findings complement other studies (Cunningham 2009;Fink et al 2001) in showing the benefits of a proactive culture of diversity.…”
Section: Hypothesis Testingsupporting
confidence: 81%
See 1 more Smart Citation
“…Specifically, the responses to quid pro quo harassment were stronger in proactive athletic departments (M=4.32, SD=.85) than they were in compliant departments (M=4.00, SD=1.00), d=.35. Thus, while organizational culture did not have direct effects, these findings complement other studies (Cunningham 2009;Fink et al 2001) in showing the benefits of a proactive culture of diversity.…”
Section: Hypothesis Testingsupporting
confidence: 81%
“…Given that compliant and proactive cultures are most different, we limit our focus to these two diversity cultures. Research set in the U.S. suggests organizations with proactive cultures feature different practices than organizations with compliant approaches to diversity management (Cunningham 2009;Fink et al 2001). For example, an organization with a culture that values cultural and views demographic differences as assets provides an environment where women and employees of color are accepted and respected, as are their contributions to the workplace.…”
Section: Studymentioning
confidence: 99%
“…Results from their study also support this position, as the correlation between proactive and compliant cultures was weaker than the corresponding relationship between proactive and reactive cultures. Our second reason is empirical in nature, as researchers have continually observed that proactive cultures and compliant cultures are significantly associated with subsequent outcomes (Fink et al 2001(Fink et al , 2003; see also Cunningham 2009), while the same cannot be said for reactive cultures. Given this evidence, we examined the effects of proactive and compliant cultures and limit our remaining discussion accordingly.…”
Section: Organizational Culturementioning
confidence: 97%
“…Fink and Pastore's (1999) model can be integrated with the literature related to organizational culture and sexual harassment. Organizations with proactive cultures feature different practices than organizations with compliant approaches to diversity management (Fink et al 2001(Fink et al , 2003. For example, an organization with a culture that values cultural and considers demographic differences as assets would provide an environment where women and their contributions to the organization will be accepted, respected, and valued.…”
Section: Organizational Culturementioning
confidence: 99%
“…Indeed, White, Protestant, able-bodied, heterosexual males possess most, if not all the power within sport and sport organizations (e.g., Cunningham 2008;Fink et al 2001). …”
Section: Role Modelingmentioning
confidence: 99%